Politik Hukum Amandemen UUD 1945 Dan Sistem Pemerintahan - Peri Pirmansyah (Jurnal Hukum IUS QUIA IUSTUM, 2007)
Normatively the amendment of Indonesian Constitution 1945 implemented pure presidential system. However, the sytewm is not compatible with the multy parties system which is viasible based on the amendment. Thus, to maintain the presidential system, it needs further regulations in the form of Act  concerns to more simple  party system to support presidential system.